Encapsulation of superparamagnetic nanoparticles into red blood cells as new carriers of MRI contrast agents. (February 2011) - Antonelli, Antonella; Sfara, Carla; Manuali, Elisabetta; Bruce, Ian J; Magnani, Mauro
Aims: The half-life of superparamagnetic iron oxide nanoparticles in the bloodstream is very short since they are rapidly taken up by the reticuloendothelial system. In this article, we report the encapsulation of different magnetic nanoparticles into human erythrocytes to increase their blood circulation time.Materials & methods: Newly synthesized and commercially available nanoparticles were evaluated for the encapsulation into red blood cells through the transient opening of membrane pores by controlled hypotonic dialysis and successive isotonic resealing and reannealing of cells.Results: Commercial superparamagnetic iron oxide nanoparticles (SHU 555A, AMI 227 and PMP-50) dextran or carboxydextran coated can be successfully loaded into red blood cells; similarly, some of the new nanomaterials, such as Np-1 nanoparticles dispersed in the Disperbyk ®® -190 agent, can be efficiently encapsulated into red blood cells.Conclusion: A careful consideration of magnetic nanoparticles parameters, such as size, synthesis protocols, coating and/or dispersant agents, is required in order to obtain efficient loading through the cell membrane pores.